WATER METHOD PREGNANCY EXERCISES TO REDUCE PREGNANCY BACK PAIN AQUATIC GYMNASTICS - Satriawan Chan, A. Apri; Suardi, Sandy; Hidayat, Arif (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2024)
Ten percent of pregnant women have chronic pain, and up to fifty percent have back discomfort. As the six-month mark approaches, 80% of pregnant women will at some point feel back pain, which is mostly due to changes in the spinal muscles (70%). Compared to weight-bearing exercise without the water method, the water pregnant exercise method is more strenuous and has a lower failure rate. Because they are submerged in water, this exercise improves thermoregulation and gives them a sense of lightness and comfort when moving. In addition, hydrostatic pressure may be able to prevent and treat lower back pain and lessen edema.